Optimizing the learning potential for the distance learning students - Focusing on the tension between experience and competence. An analysis of nursing education offered in three different learning programmes. The focus is on analysing the distance learning programme in relation to the other learning programmes. - Trine Ungermann Fredskild (FernUniversität Hagen, 2008)
The distance learning programme has made its entrance into nursing education, and many see it as a break with the education's traditions of teaching in the classroom, in practise rooms and at the patient's bedside (Chaffin & Maddux 2004)(5).Traditionally, many of the technical skills and personal qualities that nurses must acquire are learned through interaction with others. The distance learning programme has therefore given rise to some new problems and challenges, and this article discusses some of these.Empirically, the article builds on a comparative study of three student nurse classes from two Danish nursing schools, including one based on the distance learning programme. By following both distance learning and traditional nursing students in their clinical training, light is cast upon the differences and similarities that may exist in the clinical skills and competences that the students gain under the two programmes.Theoretically the article builds on Etienne Wengers theory on learning in communities of practice, focusing on the relationship between experience and competence in learning related communities of practice (Wenger 1998; Wenger 2004)(36)(37).The article contributes with findings that are related to the differences between the programmes and the different types of students that each programme attracts. The article argues that an increased didactic and pedagogical focus upon the field of tension between experience and competence will enable an optimisation of the learning conditions of the distance learning students in their clinical teaching. The article, in conclusion, thus places focus on the questions surrounding teaching design in relation to the distance learning programme.